2019
DOI: 10.1186/s12905-019-0862-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cervical cancer screening service utilization among commercial sex workers in Northwest Ethiopia: a case-control study

Abstract: BackgroundAlthough an opportunistic approach of cervical cancer screening strategy had been implemented in Ethiopia, utilization of screening services among women is still low, accounted < 1%. We hypothesize that commercial sex women in Ethiopia faced a number of obstacles in order to access screening services. Identifying the predictors influencing utilizations of the screening services is an essential effort to tailor screening program towards increasing the utilization.MethodsAn unmatched case-control study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
4
18
1
Order By: Relevance
“…Primarily, among 24 studies, two case-control studies [24,41] were not considered in the prevalence estimation. Additionally, three studies [20,22,26] were excluded from prevalence estimation after checking funnel plot and the significance of Egger's regression test.…”
Section: Meta-analysis Publication Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Primarily, among 24 studies, two case-control studies [24,41] were not considered in the prevalence estimation. Additionally, three studies [20,22,26] were excluded from prevalence estimation after checking funnel plot and the significance of Egger's regression test.…”
Section: Meta-analysis Publication Biasmentioning
confidence: 99%
“…Five studies were included in this category of metaanalysis [24,30,31,41,42]. The likelihood of screening for cervical cancer among women with history of multiple sexual partners were 5.01 times (OR = 5.01, 95% CI: 2.61, 9.61) more likely to be screened for cervical cancer as compared to their counter parts.…”
Section: Relationship Between History Of Multiple Sexual Partners Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, female commercial sex workers (FCSW) differ from one place to another 2 . Commencementreasons into that business is still personal 1 but in developing countries, poverty 3 , lack of employment, civil war was mainly noted to be the courses 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Most FCSW deal with infection preventions and leave aside consideration about their reproductive health concerns 23 . 23.7% of women in Ethiopia with cervical cancer were noted to engage themselves in commercial sex workwhich showed that, they were predisposed 4 . Study done in India alsorevealedpredicament in counselling FCSW on how to breast-feed as they are constant at risk of being infected, hence most of them lack prenatal services as well as breast-feeding recommendation 24 .…”
Section: Introductionmentioning
confidence: 99%